SINONIM DALAM MEDAN MAKNA ‘MENYAKITI’ DALAM BAHASA SASAK DIALEK NGENO-NGENE - Nisawtul Hasanah (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2017)
This study is aimed to describe synonyms of the word “to hurt” in context of Sasak language of Ngeno-ngene dialect.  The study used ethnolinguistics approach, assigning native speakers of Sasak language that spoke Ngeno-ngene dialect residing in Mamben Lauk, Wanasaba.  Data were collected using observation, interviews and document analysis.  The study revealed that vocabulary items of Sasak language using Ngeno-ngene dialect were indigenous, no reference in Bahasa Indonesia appeared in this context.  This potential can give contribution to deepen variety of diction in Bahasa Indonesia.